Assessment of Potential Risk Factors for 2019-Novel Coronavirus (2019-nCov) Infection among Health Care Workers in a Tertiary Care Hospital, North India. (March 2021) - Sharma, Sugandhi; Mohindra, Ritin; Rana, Kirtan; Suri, Vikas; Bhalla, Ashish; Biswal, Manisha; Singh, Mini P.; Goyal, Kapil; Lakshmi, Pinnaka Venkata Maha
Introduction: Health care workers (HCWs) are at the forefront to fight against COVID-19 pandemic. They are at more risk of contracting the infection. This study was planned to assess potential risk factors of 2019-novel coronavirus infection among HCWs working in a health facility and to evaluate the effectiveness of infection prevention and control measures among them. Methods: A study was conducted in a tertiary care hospital among HCWs who were directly or indirectly involved in the management of a confirmed or suspected case of COVID-19. The socio-demographic characteristics, history of exposure, IPC measures followed and clinical symptoms were compared between health care workers in COVID and non-COVID areas. Results: Majority (45%) of HCWs were nurses, followed by hospital/sanitary/technical attendants (30%) and doctors (24%). Out of a total of 256 HCWs, 2% tested positive. Around 80% of HCWs had ever attended any IPC training. A statistically significant association was found between posting area of HCWs and their exposure to COVID patients (duration of exposure, PPE has worn by HCWs, direct contact of HCWs with the patient's material) and COVID positivity ( P value <.001). Conclusion: If health care workers were trained and take adequate precautions then the risk of getting an infection is minimized.